Heightened risk of second primary carcinoma of the head and neck following cervical neoplasia. Issue 8 (4th October 2013) - Dost, Fatima; Ford, Pauline J.; Farah, Camile S.
Abstract Background Cervical cancers have been shown to increase the risk of cancers at distant sites, including the head and neck region. This study investigated the relative risk of developing head and neck cancer subsequent to cervical cancer in an Australian population. Methods Cervical cancers, head and neck cancers, and cervical dysplasias among women registered with the Queensland Oncology Repository were identified for the period 1982 to 2008. Results Over the 26‐year period, 3328 women were diagnosed with a cervical cancer and followed up for 30, 375 person‐years at risk. Eighteen women (0.5%) developed head and neck cancer within a mean time of 8.1 years (SD = 5.56). The relative risk of head and neck cancer development subsequent to cervical cancer was 6.7 (95% confidence interval [CI], 4.06–10.91). Conclusion This study demonstrates that women with cervical cancer were almost 7 times more likely to develop head and neck cancer compared to the general female population. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1132–1137, 2014